Characteristics and pathogenesis of Koebner phenomenon - Zhang, Xiaolin; Lei, Li; Jiang, Ling; Fu, Chuhan; Huang, Jinhua; Hu, Yibo; Zhu, Lu; Zhang, Fan; Chen, Jing; Zeng, Qinghai (Experimental dermatology, 2023)
The Koebner phenomenon, also known as isomorphic reaction, refers to the development of secondary lesions with the same clinical manifestations and histopathological characteristics as the primary lesions in normal skin after trauma or other stimuli. The triggering factors of Koebner phenomenon include physical trauma, chemical stimulation, mechanical stress, iatrogenic stimulation and pathogenic infection. Vitiligo, psoriasis and lichen planus are considered true Koebner phenomenon. Recent studies have shown that immunological disorders, oxidative stress, defective melanocyte adhesion and growth factor deficiency are the main pathological mechanisms of vitiligo Koebner phenomenon. In psoriasis, triggers may drive skin inflammation to induce a psoriatic phenotype through multiple signalling pathways and thereby cause Koebner phenomenon in susceptible individuals. Significantly, keratinocytes mediate the occurrence of Koebner phenomenon in psoriasis through mechano‐induced signalling pathways after sensing mechanical signals and explains the high frequency of psoriasis lesions on the extensor side of the elbow and knee joints. On the contrary, TRPA1‐driven mechano‐transduction, autoimmunity and actinic damage are the underlying mechanisms of Koebner phenomenon in lichen planus. In this review, we have summarized the current understanding of the characteristics and pathogenesis of Koebner phenomenon.